Dança de salão como possibilidade de qualificação das relações (intra) interpessoal na empresa - Silva, Caroline Rodrigues da (2011)
Thisstudy aimed tounderstand the importanceof ballroom dancingas a possibility to the qualificationof interpersonal relationshipsin the company.As specific objectives, we sought to analyze the (intra) interpersonalrelationshipsof ballroom dancing practicesin the companyand analyzesocial dancing as an experience able to qualifytheinterpersonal relationships, promoting new opportunities forinterventionsin the company. In a qualitative perspective, a methodologyof action research was used tocarry out acooperative research, inconducting focus groups-Gatti (2005) andGaskell (1999) andfor data analysis Moraes Discourse Textual Analysis and Galiazzi (2007) was used. The main authorswereDantas (2005, 1999), Rego (2008), Rey (2005),Chanlat (2007), Jesus (2000).The results showed that: perception of subjectivity exists behind the worker, and overcoming the dismissal of a sedentary lifestyle, the importance of peer relationships, the feeling of bliss and increased morale caused by the dance, the relationship between dance and life and the ballroom dancing as a promoter of respect from the link constituted by trust and self-esteem, encouraged by the self-knowledge.